Embedding Social Emotional Learning into Experiential Learning: Experiences of College Students with Mental Health Problems - Aini Mahabbati; Elya Marfu’atun; Wening Prabawati (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
This study explores the experiences of five third-year students in the Special Education Study Program at FIP UNY who experienced severe depression and high anxiety while taking the “Teaching Children with Emotional and Behavior Disorders” course. This course design integrates social-emotional learning (SEL) with experiential learning (EL) to support the academic success of students with mental health problems (high anxiety and severe depression). This exploratory qualitative study employed semi-structured in-depth interviews (lasting 40–60 minutes) with five students who were selected through screening using the PHQ-9 and GAD-7 (scores≥15). Data were analyzed with NVivo 12 Pro through open coding to identify themes, with validity checks conducted through member checking, audit trails, and reflexive memoing. Results showed that four out of five students responded positively to the learning process that integrated SEL–EL. They found it easier to understand the material, were more confident in expressing their opinions, and felt more confident in facing assignments. Emotional dynamics (active participation and self-efficacy) were also apparent: most felt more comfortable and open in discussions, although some were constrained by classroom noise, a preference for lecture methods, or feelings of inferiority compared to more capable peers. This study concludes that the integration of SEL–EL contributes to increased active participation and academic self-efficacy among students with depression and anxiety. The practical implication is the importance of course design that includes brief emotional reflection, gradual assignments with clear criteria, and fair participation protocols.